2021
DOI: 10.1111/nph.17815
|View full text |Cite
|
Sign up to set email alerts
|

Tree allocation dynamics beyond heat and hot drought stress reveal changes in carbon storage, belowground translocation and growth

Abstract: Heatwaves combined with drought affect tree functioning with as yet undetermined legacy effects on carbon (C) and nitrogen (N) allocation.We continuously monitored shoot and root gas exchange, δ 13 CO 2 of respiration and stem growth in well-watered and drought-treated Pinus sylvestris (Scots pine) seedlings exposed to increasing daytime temperatures (max. 42°C) and evaporative demand. Following stress release, we used 13 CO 2 canopy pulse-labeling, supplemented by soil-applied 15 N, to determine allocation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…C and N metabolism closely interact with each other in plant growth, productivity, and stress resistance [84,85]. Compared to C dynamics, information on post-stress responses of N contents and partitioning in trees is extremely scarce, despite this knowledge being of particular importance for predicting the resilience of forests under climate change conditions [31,86]. The total N contents observed in this study were in the range previously found in European beech and fir [33,53,[87][88][89].…”
Section: Memory Effects On Carbon and Nitrogen Metabolismsupporting
confidence: 61%
“…C and N metabolism closely interact with each other in plant growth, productivity, and stress resistance [84,85]. Compared to C dynamics, information on post-stress responses of N contents and partitioning in trees is extremely scarce, despite this knowledge being of particular importance for predicting the resilience of forests under climate change conditions [31,86]. The total N contents observed in this study were in the range previously found in European beech and fir [33,53,[87][88][89].…”
Section: Memory Effects On Carbon and Nitrogen Metabolismsupporting
confidence: 61%
“…As a result, T and VPD have been identified as increasingly important drivers of plant hydraulic conductivity losses (Olson et al, 2020 ), growth reduction (Trotsiuk et al, 2021 ), plant mortality (Adams et al, 2009 ; Allen et al, 2015 ) and reduced ecosystem productivity (Ciais et al, 2005 ). Many studies focus on plant responses to a combination of soil drought and either high T (‘hot droughts') (Allen et al, 2015 ; Cochard, 2019 ; Grossiord et al, 2018 ; Rehschuh et al, 2021 ), or high VPD (Anderegg & Meinzer, 2015 ; Eamus et al, 2013 ; Fontes et al, 2018 ). For example, high VPD combined with soil drought leads to extreme xylem tensions and embolisms (Tardieu & Simonneau, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the frequency of drought events is predicted to increase in the future (IPCC, 2021), recovery from these events is an important aspect of tree survival, which has attracted less attention compared with direct drought effects (Ruehr et al, 2019). On the one hand, drought release can increase aboveground C sink activity for repair processes such as growth of new xylem and embolism refilling (Brodersen & McElrone, 2013; Ruehr et al, 2019; Zang et al, 2014) or C storage to prepare for future droughts (Galiano et al, 2017; Rehschuh et al, 2021). On the other hand, drought release can stimulate belowground C sinks such as root production, mycorrhizal and microbial activity, and associated soil respiration (Brunner et al, 2019; Gao et al, 2021; Hagedorn et al, 2016; Joseph et al, 2020; Werner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%